All-Trans Retinoic Acid Grafted Poly Beta-Amino Ester Nanoparticles: A Novel Anti-angiogenic Drug Delivery System - Nadia Karimi; Kamaran Mansouri; Mohammad Soleiman-Beigi; Ali Fattahi (Tabriz University of Medical Sciences, 2020)
Purpose: Developing chemotherapy with nanoplatforms offers a promising strategy for effective cancer treatment. In the present study, we propose a novel all-trans retinoic acid (ATRA) grafted poly beta-amino ester (PBAE) copolymer for preparing nanoparticles (NPs). Methods: ATRA grafted PBAE (ATRA-g-PBAE) copolymer was synthesized by grafting ATRA to PBAE; it was characterized by proton nuclear magnetic resonance, Fourier transform infrared, and thermogravimetric analysis. ATRA-g-PBAE NPs were prepared by the solvent displacement method. Design-Expert software was employed to optimize size of NPs. The morphology was evaluated by transmission electron microscope, and ultraviolet-visible spectroscopy was applied for drug release. Cytotoxicity was evaluated toward HUVEC cell line, and the 3D collagencytodex model was used to evaluate anti-angiogenic property of PBAE, ATRA, and NPs. Results: The optimum size of the NPs was 139.4 ± 1.41 nm. After 21 days, 66.09% ± 1.39 and 42.14% ± 1.07 of ATRA were released from NPs at pH 5.8 and 7.4, respectively. Cell culture studies demonstrated antiangiogenic effects of ATRA-g-PBAE NPs. Anti-angiogenesis IC50 was 0.007 mg/mL for NPs (equal to 0.002 mg/mL of ATRA) and 0.005 mg/mL for free ATRA. Conclusion: This study proposes the ATRA-g-PBAE NPs with inherent anti-angiogenic effects as promising carrier for anticancer drugs with purpose of dual drug delivery.